Mechanisms of myofibrillogenesis and sarcomere formation in cardiomyocytes - Kobeza, P.A.; Tverdokhlib , I.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Relevance. The formation of sarcomeres and the organization of myofibrils are critically important for the contractile function of cardiac muscle and underlie normal heart development. Understanding the principles of their self-organization provides essential insights into cardiac tissue morphogenesis and fundamental cell biology. Objective. To systematize data on the mechanobiological processes underlying the normal formation of sarcomeres and myofibrils in cardiomyocytes, with a focus on the roles of mechanical tension, mitochondria, and intercalated discs. Methods. A comprehensive review of current scientific literature on sarcomere and myofibril structural development was conducted. The analysis summarizes findings from morphological, biophysical, and molecular biology studies, primarily using in vivo models. Results. Sarcomere formation is a dynamic process coordinated by mechanical tension, which organizes actin and myosin filaments with the involvement of titin. Myofibrils mature in close association with mitochondria, whose architecture adapts to the energetic demands of the cell. Studies show that myosin motor activity is required for the formation of long, aligned myofibrils, while actin-binding proteins stabilize these structures locally. Intercalated discs serve not only as mechanical junctions between cardiomyocytes but also as morphogenetic zones for the insertion of new sarcomeres, ensuring growth and structural ordering in response to mechanical load. Conclusion. Myofibrillogenesis is a multi-level process that integrates mechanical cues, molecular interactions, and cellular architecture. Further research should focus on the mechanisms of sarcomere self-organization in different types of muscle tissue under normal and abnormal development.